Above-threshold ionization for very low electron energy. (26th June 2015) - Becker, W; Milošević, D B
Abstract: The rescattering term of the ionization amplitude in the strong-field approximation is analyzed for very low electron energy and emission in arbitrary direction, first in terms of the classical simple-man model and then in the quantum-mechanical quantum–orbit expansion of the strong-field-approximation amplitude. Particular orbits can be associated with particular patterns in the velocity map. The different roles of forward and backscattering are investigated. In addition to known features such as the LES and the fork, a characteristic and pronounced V structure in the velocity map is identified, which has been observed in recent experiments (2014 Phys. Rev. A 90 063424 ).